Social Network Dynamics and Psychological Adjustment Among University Students - Fukukawa, Yasuyuki (Universitas Ahmad Dahlan, 2013)
Abstract The present study investigated the social network structure in a university class and how it changed over time. In addition, student rankings of social status in the class based on different network centrality measures were compared, and associations between studentsâ social status and psychological adjustment were evaluated. One university seminar class in which ten juniors and ten seniors were enrolled was followed for six months. Although the class network consisted of some disconnected subgroups at baseline, it became a single group at follow-up. In addition to these structural changes, measures of network integration (density and transitivity) also increased from baseline to follow-up. Comparisons of centrality measures indicated that the information centrality measure best captured the network infrastructure compared to the betweenness, closeness, and degree centrality measures. Furthermore, among the centrality measures, information centrality had the most stable positive association with psychological adjustment. Theoretical and practical implications of these peer network dynamics and adjustment issues are discussed. Keywords: social network, centrality, psychological adjustment, classroom climate